MODALITY IN TORAJA LANGUAGE - Jusmianti Garing (Metalingua: Jurnal Penelitian Bahasa, 2014)
TORAJA language is still being used nowadays by the people in daily communicationamong them. Toraja language is known as the language that has a lot of linguisticfeatures and it is very interesting to study further, so it can contribute to knowledgeregarding language in general and Toraja language specifically. Furthermore, thelinguistic features in Toraja language has many implied meanings that are used asguidelines in their lives and a manifestation of Toraja people who owns high ethics andunique culture. Based on such argument, this writing aims to describe one of languagefeatures in Toraja language, namely modality systems. This is descriptive qualitativestudy using literature study. Such method aims to find detail and complete data. Moreover,this writing is analysing Toraja discourses that contain folklore, fable, and sage. Theresult shows that modality forms in Toraja are marked by auxiliary verbs, particles,and negations. The auxiliary verbs are la-, innang,bela, and maqdin. Particles arebang, omi, sia, and suffixes –ri, –ra –mi,-mo-, and –pa. Negations are taeq,daq, andtang. All of the forms function as epistemic and deontic modality.